PENGEMBANGAN MEDIA WORDWALL BERBASIS CANVA UNTUK MENINGKATKAN MINAT BELAJAR SISWA KELAS IV MI NURUL HASANAH KOTA MAKASSAR - Aliah, Nur; Rohana; Ahmad Syawaluddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop a Canva based Wordwall learning media and analyze its feasibility and effectiveness in increasing the learning interest of fourth-grade students at MI Nurul Hasanah, Makassar City. The method used in this study is Research and Development (R&D) with the ADDIE development model which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of 22 fourth-grade students and 1 class teacher. Data were collected through questionnaires, interviews, and documentation. Qualitative data were obtained from suggestions and input from material experts, media experts, and respondents, while quantitative data were analyzed using a Likert scale and descriptive analysis. The results of the study indicate that students' need for learning media is in the high category, with 72.73% of students categorized as very needy and 27.27% categorized as needy. The resulting product is a Canva-based Wordwall learning media that was systematically developed according to the ADDIE stages. The results of the feasibility test show that the media is categorized as very feasible, with a percentage of assessment by material experts of 85.93% and media experts of 89.58%. In addition, the use of this media has been proven to increase student learning interest, as indicated by an increase in scores from 1105 before use to 1705 after use. It can be concluded that the Canva-based Wordwall media is feasible and effective to be used as an interactive learning alternative to increase student learning interest in science subjects in elementary schools.